Why crowdsourcing fails - Linus Dahlander; Henning Piezunka (Journal of Organization Design, 2020)
Crowdsourcing-asking an undefined group of external contributors to work on tasks-allows organizations to tap into the expertise of people around the world. Crowdsourcing is known to increase innovation and loyalty to brands, but many organizations struggle to leverage its potential, as our research shows. Most often this is because organizations fail to properly plan for all the different stages of crowd engagement. In this paper, we use several examples to explain these challenges and offer advice for how organizations can overcome them.
Keywords: 650; Crowdsourcing; Organizational design; Innovation